Many moons - Thurber, James, 1894-1961.; Slobodkin, Louis, 1903-1975 (San Diego : Harcourt Brace, 1991)
Though many try, only the court jester is able to fulfill Princess Lenore's wish for the moon.
Art techniques used: Lightly colored, playful drawings in pen, ink, pencil and watercolor.
"Voyager books."
The Caldecott medal.
Keywords: Princesses -- Fiction; Moon -- Fiction; Caldecott Medal; Princesses -- Juvenile fiction; Moon -- Juvenile fiction